2022
DOI: 10.1111/odi.14390
|View full text |Cite
|
Sign up to set email alerts
|

Salivary biomarkers in burning mouth syndrome: A systematic review and meta‐analysis

Abstract: The International Classification of Orofacial Pain (ICOP) defines burning mouth syndrome (BMS) as "an intraoral burning or dysaesthetic sensation, recurring daily for more than 2 h/day for more than 3 months, without evident causative lesions on clinical examination and investigation" (ICOP, 2020). BMS affects 4% of the general population and 18%-33% of all postmenopausal women (Acharya

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 60 publications
1
10
0
Order By: Relevance
“…In this systematic review, our results showed this biomarker in saliva was significantly higher in patients with BMS compared with healthy people. This result was in line with the previous meta‐analysis study which showed the relationship between BMS and biomarker of cortisol 67 . Furthermore, the level of anxiety was also statistically higher in BMS individuals, which indicated that it may be related with the level of cortisol.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In this systematic review, our results showed this biomarker in saliva was significantly higher in patients with BMS compared with healthy people. This result was in line with the previous meta‐analysis study which showed the relationship between BMS and biomarker of cortisol 67 . Furthermore, the level of anxiety was also statistically higher in BMS individuals, which indicated that it may be related with the level of cortisol.…”
Section: Discussionsupporting
confidence: 91%
“…This result was in line with the previous meta-analysis study which showed the relationship between BMS and biomarker of cortisol. 67 Furthermore, the level of anxiety was also statistically higher in BMS individuals, which indicated that it may be related with the level of cortisol. The neurotrophic and neuroprotective actions of cortisol might be alleviated in response to increase the salivary cortisol levels, contributing to the chronic pain of BMS.…”
Section: Discussionmentioning
confidence: 89%
“…Cortisol is a hormone released by the adrenal cortex which regulates homeostasis during emotional and physical stress. Cortisol, along with αamylase, has been studied as a major biomarker of BMS [25]. Patients with BMS presented higher salivary cortisol levels than the control group [26].…”
Section: Discussionmentioning
confidence: 99%
“…The levels of T3, T4, and TSH have been studied to in uence the presence or severity of BMS symptoms [31]. However, a recent systematic review examined the usefulness of 54 biomarkers, which are largely divided into (1) pain biomarkers (including estradiol, progesterone, DHEA, and substance P), (2) stress biomarkers (including cortisol and α-amylase), (3) in ammatory biomarkers, (4) trace elements, anions, and chemical compounds; and (5) others, among whom only stress biomarkers were reliable [25]. In this study, the presence of psychological stress was found to further enhance cortisol's role as a predictor of BMS.…”
Section: Discussionmentioning
confidence: 99%
“… 32 Generally, compared with healthy people, patients with BMS have lower levels of DHEA and higher levels of cortisol. 33 , 34 Therefore, salivary cortisol and DHEA can be used as saliva biomarkers to evaluate stress in patients with oral mucosal diseases.…”
Section: Neurobiological Mechanismsmentioning
confidence: 99%